Aspects of Style and Meaning in Selected Poems of Niyi Osundare - Olaluwoye, Layo Esther; Ugwu, Chinonye Ekwueme - (NIU Journal of Humanities, 2020)
The majority of studies on the poetry of Niyi Osundare has concentrated mostly on thematic aspects, keeping silent on how figurative and linguistic resources are utilized to create an identity for the poet and negotiate meaning in his work. This study, therefore, investigated the use of language in context-specific ways to explore the aspects of meaning and style in Osundare’s poetry. The study is anchored on the theoretical underpinnings of Halliday’s Systemic Functional Grammar. The study revealed how figurative devices such as alliteration and assonance; imagery and its various types are deliberately deployed by the poet to effectively encode the meaning of the texts under study and to achieve aesthetic value, in relation to context of situation and textual function. The figurative devices identified in the study are deployed to convey the intentions of the poets, issues raised in the poems and they contribute to meaning clarification in the texts. Keywords: Figurative devices, linguistic resource, osundare, style